Kode Vicious In Praise of the Disassembler: There is much to be learned from the lower-level details of hardware. - Neville-Neil, George V. (Communications of the ACM, 2021)
The article provides an answer to a question concerning computer code and the potential implications of a bug that appears in the binary due to a mistake by one part of the tool chain.